Photon management in solution-processed organic light-emitting diodes: a review of light outcoupling micro- and nanostructures - Gomard, Guillaume; Preinfalk, Jan B; Egel, Amos; Lemmer, Uli (Journal of photonics for energy, 2016)
To allow a greater acceptance in the display and lighting markets, organic light-emitting diode (OLED) technology is currently the subject of intensive research efforts aimed at manufacturing cost-effective devices with higher efficiencies. In this regard, strategies matured in the field of photonics and nanophotonics can be applied for photon management purposes to improve the outcoupling of the generated light and to control the emission pattern. In this review, we report on the recent experimental and numerical advances to pursue those goals by highlighting the example of bottom-emitting devices. The cases of periodical micro- and nanostructures, as well as of stochastic ensembles that can be easily implemented using printing techniques, are covered herein. It is shown that beyond the sole optical properties, such additional elements can simultaneously improve the electrical characteristics of solution-processed OLEDs, and thus enable an optimization of the devices at different levels.